Strengthening Character Education Through Counseling Guidance Management SMA Bunda Hati Kudus - Daempal, Yoseph Silvanus; Matin, Matin; Kamaluddin, Kamaluddin (Journal of Education Research and Evaluation, 2021)
The management of BK services at SMA Bunda Hati Kudus Jakarta is managed by a congregation of nuns who are unique in the management of their school and the spirit or spirituality that animates the congregation. The purpose of this study is to determine the function of BK service management in strengthening character education. The descriptive research method develops conditions as a whole so that in this study there is no sample, but takes the whole subject according to the objectives. The approach is qualitative, to be able to describe the research subject in more depth and to know the real phenomena that exist in the field. The data were collected qualitatively through interviews, observation, and documentation. Data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions and verification. To obtain data validity, data triangulation was carried out. The results show that: (a) BK service planning is right on target, (b) BK teachers at the implementation stage go according to plan because of their awareness of their duties, (c) BK service implementation is based on the program, but some programs cannot be implemented properly. good, (d) the principal's supervision of the BK service program is not optimal.